Faktor-Faktor yang memengaruhi pernikahan dini di Indonesia - Adinda Hermambang; Choirul Ummah; Eunike Sola Gratia; Fathul Sanusi; Wilda Maria Ulfa; Rani Nooraeni (Jurnal Kependudukan Indonesia, 2021)
One of the social problems that existed in Indonesia is high rates of early marriage or child marriage. Based on its absolute number, Indonesian has been one of top ten country with the highest number of child marriage all over the world. Early marriage is defined as a marital union by women under 16 years old. Many factors affect early marriage, such as education factor, economy factor, and culture factor. Furthermore, early marriage may have effects on deteriorating physical and psychological health, low educational attainment, and increasing risk of domestic violence. By utilising 2017 IDHS dataset, this study aims to examine the determinants of early marriage in Indonesia. This study applies binary logistic regression method for the data analysis. The results of this study show that variables significantly affect the status of early marriage are marital status at the first sexual intercourse, residential type, partner’s working status, women’s education, and partner’s education. Moreover, variables that do not significantly affect the status of early marriage are women’s working status, wealth index, and interaction between women’s education and wealth index.